Place and behavior: The role of accessibility. (June 2019) - Bugden, Dylan; Stedman, Richard
Abstract: We address the implications of a latent yet critical assumption in place research: that sense of place is chronically accessible in memory. It is presently assumed that sense of place is a consistently retrieved representation stored memory that is always at the "top of the mind", with an automatic, inevitable, and robust effect on behavioral outcomes. This assumption is at odds with research in social psychology which asserts that most mental constructs are only temporarily accessible. That is, constructs are often formed on the spot, and compete with other constructs for applicability to a judgment or behavior. We argue that this assumption partially explains the inconsistencies identified in recent reviews of research on the behavioral outcomes associated with person-place bonds. We conclude with an outline of a research program that builds on an assumption of temporary accessibility to explain the relationship between place and behavior. By focusing on the temporary accessibility of place, we can better understand the dynamic interaction between social and psychological factors in shaping person-place bonds. Highlights: Sense of place tends to be viewed as chronically accessible. Temporary accessibility is a more realistic assumption. Temporary accessibility helps explain variation in findings on place-related behavior. We provide a new foundation for the study of place and behavior.